If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3X + -1) + -8X = -8 Reorder the terms: 4(-1 + 3X) + -8X = -8 (-1 * 4 + 3X * 4) + -8X = -8 (-4 + 12X) + -8X = -8 Combine like terms: 12X + -8X = 4X -4 + 4X = -8 Solving -4 + 4X = -8 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4X = -8 + 4 Combine like terms: -4 + 4 = 0 0 + 4X = -8 + 4 4X = -8 + 4 Combine like terms: -8 + 4 = -4 4X = -4 Divide each side by '4'. X = -1 Simplifying X = -1
| -6+5=x-23 | | 7y-4=3x+16 | | -10x-42=128 | | 8-6(4d+18)=-19-18-17d | | 4(-14+4y)-2y=14 | | 4(20x+50)=840 | | 2k-6k=3(7-2k)-7(8k+3) | | 4.5b-5.25b+3=3.75 | | (x^2-2x-2)(x^2-12x+37)=0 | | y=9.5(20)+100 | | 12x=46-6x | | 50-3x=15+2x | | 4.5+5.25+3=3.75 | | 4x+17=-2x+3 | | 2x^2-14=-64 | | 3x-5=6x-5 | | 92-20=9h | | y=9.5x+100 | | n+0.5=-2.833 | | 4.5b-5025b+3=3075 | | 15=-6+4(d+3) | | -16-t=7 | | (3-2x)=7 | | 6+6x-10=-20 | | 6x-10x=10x-10x-2 | | -17r+8=42 | | -4(3x+3)=7x-2 | | 2y=-172-6x | | -4h+8=36 | | 3(2x+3)=4(x-6) | | 2-.33x=26 | | 18(6m+7)=-9(8m+6) |